2020
DOI: 10.28945/4536
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Engagement in Online Brand Communities: Community Values, Brand Symbolism and Social Strategies

Abstract: Aim/Purpose: This study examines the kind of community value companies should provide when strengthening the relationship between customers and brands through the establishment of an online brand community, and how this kind of community value promotes customers’ sense of community engagement and willingness to spread brand reputation. The paper also discusses how an enterprise’s brand symbolism affects the relationship between community value and customers’ engagement in online brand community. This study exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The impact of engagement on behavioral intentions is supported by prior research (Pan, 2020). Fan et al (2017) reported that engagement in information systems is a strong indicator of information systems dependence.…”
Section: Research Modelmentioning
confidence: 67%
“…The impact of engagement on behavioral intentions is supported by prior research (Pan, 2020). Fan et al (2017) reported that engagement in information systems is a strong indicator of information systems dependence.…”
Section: Research Modelmentioning
confidence: 67%
“…M‐shopping apps offer a unique possibility for retail, tourism, or hospitality services, stimulating, in the process, the growth of electronic markets by over 40%, where more than 90% of the purchases are done via smartphones (Comscore, 2020). The factors that guide customers towards choosing an app, look to address customers' information related to a retailer's functional components, the identity that the value drives, and/or brand‐related features (Pan, 2020; Wirtz et al, 2013). Among the most important are those that directly describe the purchasing environment (i.e., the perceived app characteristics, enticements, information accuracy, security and privacy, retailer's reputation, and purchase conditions or personalization) (Akram et al, 2020; Hanson et al, 2019; Pan, 2020; Prodanova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%